Ancient empires : from Mesopotamia to the rise of Islam - Cline, Eric H., (Cambridge University Press, 2011)
"Ancient Empires is a relatively brief yet comprehensive and even-handed overview of the ancient Near East, the Mediterranean, and Europe, including the Greco-Roman world, Late Antiquity, and the early Muslin period. The book emphasizes the central, if problematic, connection between political and ideological power in both empire-formation and resistance. By defining the ancient world as a period strectching from the Bronze Age into the early Muslim world, it is broader in scope than competing books; yet at the same time its tight thematic concentration keeps the narrative engagingly focused"--Provided by publisher.